MISOGYNIST HOSTILITIES REPRESENTATION OF THE MAIN CHARACTER IN “MARY QUEEN OF SCOTS” SCREENPLAY - FATHIA RAHMA DEWI; SISILA FITRIANY DAMANIK (LINGUISTICA, 2022)
This study aims to find out the kinds of misogynist hostility that happened to the main character and the factors that influence the misogynist hostility directed at the main character. The objective of this study is to find out: 1) To analyze the misogynist hostilities that occur to the main character; and 2) To explain the factors that are the cause of the misogynist hostilities that happened to the main character. The data on this study was the written narrative and dialogue text taken from “Mary Queen of Scots” screenplay. The findings show that:  1) There are three kinds of categorized misogynist hostilities consist of fifth-teen kinds of hostilities there are Infantilizing and Belittling (ridiculing, humiliating, mocking, slurring, vilifying, and demonizing), Sexualization and Desexualization (silencing, shunning, shaming, blaming, patronizing, and condescending), and Aggression (physical violence, intimate partner violence (IPV), and rape). 2) There are three kinds of misogynist hostilities factor that are the main factors that influence the misogynist hostilities that occurred to the main character in the screenplay. Which consist of eleventh kinds of the reasons behind the misogynist hostilities; there are anxieties, fears, and desire to preserve the patriarchal order (Threatened, cornered, thwarted, let down, wounded, undermined, ousted, surpassed, disappointed, humiliated, chastened). In conclusion, the misogynist hostilities happened to the main character because their subordinate felt anxious and feared being overpowered. Thus, they turn hostile to punish the main character for preserving the patriarchal order.